A model for the measurement an improvement of intellectual capital in the energy sector: sample application in electricity distribution company - Kayakutlu, Gülgün (My University, 2004)
Gelişmeler, kurum başarısını tanımlamak için tüm bilgi kaynaklarının değerlendirilmesini gerektirdi. Bu nedenle günümüzde performans ölçümü, finansal değerlerle entelektüel sermaye değerlerini bütünleştiriyor. Entelektüel sermaye alanında yapılan akademik çalışmalar ticari uygulamaları izleyerek geliştiğinden, yeni ölçümlerin dikey sektörlerde kullanımı yakın geçmişte başladı. Mevcut ölçüm modelleri incelendiğinde, bunların kalkınmakta olan ülkelerde, özelleştirme sürecini yaşayan enerji dağıtım kuruluşlarına tam olarak uyarlanamadıkları görüldü. Bu çalışmada, bir enerji dağıtım kurumunun rekabeti zorlayan yeni pazar tanımında başarıya ulaşabilmesi için yararlanacağı yedi adımdan oluşan bir model geliştirildi. İlk adım, işletmeyi etkileyen bilgi kaynaklarını saptayacak şekilde geliştirildi. Her olası kaynağa özel bilgiye dayalı sorgulama, Likert Ölçeğini kullanarak hazırlandı. Yanıtları değerlendirmek üzere Faktör Analiz yönteminden yararlanıldı ve sonuçta kaynakların stratejilere yüklediği değerler bulundu. İkinci adımda şirket içi stratejik analiz yapıldı ve mevcut performans değerleri öğrenildi. İlk iki analizin farkları üçüncü adımda ortaya konuldu ve entelektüel sermayeye dayalı hedefler çıkarıldı. Bu hedeflerin doğruluğu şirket içi yeni bir sorgulama ile test edildi. Testlerin sonucunda hedefler seçildi ve öncelikleri belirlendi. Beşinci adımda yapılandırılan Lineer Hedef Programlama problemi için önceki bulgular girdi olarak kullanıldı. Bu problemin çözümü ile değişik kaynaklara yapılacak yatırımın dağıtımı ve altıncı adımda incelenen iş planı elde edildi. Modelin son adımı, yeni bakış açısını geliştirmek üzere yönetime verilecek eğitimlerin saptanması ve başlatılmasını içerdi. Geliştirdiğimiz model Kayseri ve Civarı Elektrik Dağıtım A.Ş.'de uygulanarak, yöneticilerine rekabetle savaşmak üzere yeni bir vizyon sundu. Mayıs 2004Gülgün KAYAKUTLU

A MODEL FOR THE MEASUREMENT AND IMPROVEMENT OF INTELLECTUAL CAPITAL IN THE ENERGY SECTOR: SAMPLE APPLICATION IN ELECTRICITY DISTRIBUTION COMPANY Enterprise success has evolved to encapsulate all of its knowledge resource nodes. Hence, the performance is to be measured by indices that integrate financial and intellectual capital measures, which can not be defined in terms of general standards but are specific to each company. Academic studies followed practice in developing intellectual capital measures and therefore, new measures are recently applied in vertical industries. It is observed that currently implemented performance models are not perfectly fit for energy distribution companies in developing countries where privatisation is in progress. In this study, a seven phased business model was developed to guide an energy distribution company in a new competitive market to success. Initial phase of the model was reserved for defining the knowledge resources specific to the company. Knowledge based questionnaires were prepared for each knowledge resource based on the Likert Scale. Responses were analysed using Factor Analysis methods for different strategies. This phase resulted in achieving preferences loaded on activities for each strategy. The second phase was designed to complete strategic analysis and existing performance measures internal to the company. The gap analysis was carried out in the third phase to compare the previously accumulated information and define company goals. Fourth phase is benefited to validate the extracted goals through an internal survey, which set the priorities among the goals. Goal Model was developed in the fifth phase on a linear goal programming problem, where results of previous phases served as input. Solution of the problem led us to the sixth phase, which proposed a business plan for strategies with allocation of investments. Last phase was used to determine the starting point of implementation by giving managers the necessary training. The developed model was applied in KCETAŞ, Kayseri and results presented executive managers a new vision which will flourish the competitive advantages. May 2004
Keywords: Arazi ekonomisi; Ekonomi; Enerji üretimi; Performans Ölçümü; Rekabet